Deductive Thinking at the Preparatory stage Students. - et. al., Yasmine M. Hamad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to identify the extent of possessing deductive thinking among middle school students, and the researchers chose the descriptive approach. The sample consisted of (400) male and female students of the fourth scientific grade from (9) schools (preparatory and secondary) in the three directorates of al-Karkh education (first, second, and third) who were chosen by random stratification method, by (154) males and (246). Females. The researchers prepared the research tool: the deductive reasoning test that consisted of (24) items. Second, the psychometric properties of the apparent and constructive validity and reliability were verified by the internal consistency method. The following statistical methods were used: (Chi-square, the equation of difficulty and ease, the discrimination equation, the T-test for one sample, the T-test for two independent samples, the point bilateral correlation coefficient, the Pearson correlation coefficient, the Keoder Richardson equation 20, the Alpha Cronbach equation. (Middle school students have a high degree of deductive reasoning.)